Psycholinguistic Characteristics of Autists and Their Prototypes in American Cinema Discourse (Based on the Films "Rain Man" and "The Real Rain Man") - Ikalyuk, L.; Kuzmyn, O. (Journal of Vasyl Stefanyk Precarpathian National University, 2015)
The article focuses on the study of the main characteristics of people with autistic spectrum disorders. The comparison between the famous American savant, Kim Peek, and his prototype in the American cinema discourse has been made on the basis of the films Rain Man and The Real Rain Man. With the help of psychographological analysis, the speech of the man and his fictional prototype has been examined. The analysis showed that the difference between the two persons is indubitable, which can be explained by the fact that the savant syndrome was caused by different disorders.